An efficient combination of Zr-MOF and microwave irradiation in catalytic Lewis acid Friedel–Crafts benzoylation. Issue 18 (11th April 2016) - Doan, Tan L. H.; Dao, Thong Q.; Tran, Hai N.; Tran, Phuong H.; Le, Thach N.
Abstract : The catalytic activity of a highly porous and stable zirconium-based metal–organic framework in the benzoylation reaction was enhanced by microwave irradiation. Abstract : A zirconium-based metal–organic framework, an effective heterogeneous catalyst, has been developed for the Friedel–Crafts benzoylation of aromatic compounds under microwave irradiation. Constructed by a Zr(iv ) cluster and a linker 1, 4-bis(2-[4-carboxyphenyl]ethynyl)benzene (H2 CPEB), the MOF, possessing large pores and high chemical stability, was appropriate for the enhancement of Lewis acid activity under microwave irradiation. The reaction studies demonstrated that the material could give high yields for a few minutes and maintain its reactivity and structure over several cycles.